2014
DOI: 10.1371/journal.pcbi.1003890
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Sink Containing Two-Component Signaling Systems as Tunable Threshold Devices

Abstract: Synthetic biology aims to design de novo biological systems and reengineer existing ones. These efforts have mostly focused on transcriptional circuits, with reengineering of signaling circuits hampered by limited understanding of their systems dynamics and experimental challenges. Bacterial two-component signaling systems offer a rich diversity of sensory systems that are built around a core phosphotransfer reaction between histidine kinases and their output response regulator proteins, and thus are a good ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…FrzZ plays an important role in the regulation of cell reversal frequency because increasing amounts of phospho-FrzZ leads to an increase in cell reversals. In two-component systems of other species, accessory CheY-like regulators were described to act as phosphate sinks, that is, they solely accept phosphoryl-groups from a His-kinase to modulate the phosphorylation rate of the main CheY-effector of the system (Sourjik and Schmitt, 1998;Amin et al, 2014). Does a similar mechanism apply for Frz signaling?…”
Section: Regulation Of Cell Reversal Frequency 389mentioning
confidence: 99%
“…FrzZ plays an important role in the regulation of cell reversal frequency because increasing amounts of phospho-FrzZ leads to an increase in cell reversals. In two-component systems of other species, accessory CheY-like regulators were described to act as phosphate sinks, that is, they solely accept phosphoryl-groups from a His-kinase to modulate the phosphorylation rate of the main CheY-effector of the system (Sourjik and Schmitt, 1998;Amin et al, 2014). Does a similar mechanism apply for Frz signaling?…”
Section: Regulation Of Cell Reversal Frequency 389mentioning
confidence: 99%
“…Initially we compiled a list of physiological variables that are important for the function of these signal transduction circuits 9,10,[42][43][44][45][46][47]12,27,[36][37][38][39][40][41] . We compared the alternative architectures to understand how they differed with respect to each of those variables.…”
Section: Discussion Implicationsmentioning
confidence: 99%
“…For example, in the chemotaxis network of E. coli the histidine kinase CheA can phosphorylate either of the two regulator proteins CheY and CheB: while CheY-P controls the sense of rotation of the flagellar motor CheB-P mediates feedback regulation at the receptor level (Sourjik, 2004). In a recent study Amin et al (2014) have shown that phosphorylation of two response regulators by a single histidine kinase may lead to thresholds and ultrasensitivity in a similar manner as for receptor-ligand binding and phosphorylation/dephosphorylation cycles. Hence, it seems likely that substrate competition in twocomponent systems can be described by similar equations as those derived in the present study.…”
Section: Discussionmentioning
confidence: 99%